FORMATION OF COMMUNICATIVE COMPETENCE IN THE PROCESS OF FOREIGN LANGUAGE LEARNING PROFESSIONALLY (Pedagogy of Higher and Secondary Education, 2009)
The article devotes to the problem of forming communicative competence of the students in the process of learnin foreign languages professionally oriented.
Keywords: educational process; communicative competence; foreign languages professionally oriented